Anteriorna ishemična optična nevropatija kot posledica zdravljenja z interferonom alfa - Godina-Kariž, Stanka (Zdravniški vestnik, 2005)
Background. Anterior ischemic optic neuropathy rarely occurs with interferon alpha therapy. The mechanism by which interferon induces anterior ischemic optic neuropathy is unknown. Methods. A 62-year-old man presented with complaints of sudden severe loss of vision in the left eye. He has been receiving interferon alpha and ribavirin for chronic infection with hepatitis C virus. Vision loss occurred 6 months after the beginning of treatment. Afterwe ruled out other possible etiologies, a diagnosis of anterior ischemic optic neuropathy due to interferon therapy was made and the drug was discontinued. A follow up 3 weeks later showed an improvement of visual acuityand resolution of scotoma, disc hemorrhage and edema. Conclusions. The resolution of anterior ischemic optic neuropathy after discontinuation of interferon suggested a casual relation, though the pathophysiologic mechanism remains unknown. An ophthalmologic examination should be performed in patientswith risk factors of visual loss before and regularly during interferon treatment.
Keywords: Adverse Effects; Drug Therapy; Fundus Oculi; Hepatitis C; interferon; Interferon-alfa; Interferon-Alpha; izguba vida; Middle Age; Očesno ozadje; oftalmologija; Optic Neuropathy, Ischemic; Optična nevropatija ishemična; Srednja leta; Therapeutic Use; therapy; vid; zdravljenje